Association between bruxism, alcohol and tobaco use among brazilian students - Alves-Rezende, Maria Cristina Rosefini [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP]; Dekon, Stefan Fiúza de Carvalho [UNESP]; Alves-Rezende, Luis Guilherme Rosefini; Alves-Rezende, Ana Laura Rosefini; Montanher, Ingrid Silva; Cunha-Correia, Adriana Sales [UNESP]; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP] (My University, 2011)
The etiology of bruxism is not well defined. Different factors affecting the central nervous system are considered as risk factors for bruxism. Dental students are not immune to the bruxism, alcohol consumption and tobacco use, despite their training, knowledge of its effects and social responsibility. The purpose of this study was to evaluate the association between bruxism, alcohol consumption and tobacco use among Brazilian dental students. Participants were chosen among 180, 17-29 year-old students at the UNESP’s Dentistry School – Araçatuba Campus. They were divided into those with and without bruxism on the basis at validated clinical criteria. The clinical examinations were carried out by four standardized examiners (Intraexaminer and Interexaminer Unweighted kappa= 0.82, Weighted kappa= 0.89, respectively), in the clinic, with daylight and a tongue depressor. Bruxism was registered with the following categories: no wear facets, wear facets in enamel, dentine wear facets, facets wear half of the crown and wear facets more than 2/3 of the tooth crown. A self report validated questionnaire for alcohol consumption and tobacco use with 29 questions was completed by both groups. Fischer exact test and T-test were used and Odds Ratio and Confidence Interval was estimated. Bruxism was more frequent among cigarette smokers both in men (68.4%) and in women (56.8%). Among all respondents in this group, 82.6% reported that they would like to quit smoking and those who have tried previously to quit (76.4%) found it made them more stressed. Drinker was more frequent in the group with bruxism also (66.5% of the female and 73.5% of the male). 88.4% reported drinking alcohol because it “allows dealing with stress in an adequate way”. Results suggest a positive association between bruxism and alcohol consumption and tobacco use.

Diferentes fatores que afetam o sistema nervoso central são considerados de risco para o bruxismo. Universitários não são imunes ao bruxismo, consumo de álcool e uso de tabaco apesar de sua formação e responsabilidade social. Avaliou-se a associação entre bruxismo, consumo de álcool e tabaco entre graduandos de Odontologia. Foram voluntários 180 estudantes (17-29 anos) da Faculdade de Odontologia de Araçatuba/ UNESP, divididos entre aqueles com e sem bruxismo, com base em critérios clínicos validados realizados por quatro examinadores com luz natural e espátula de madeira. Bruxismo foi registrado nas seguintes categorias: sem facetas de desgaste; facetas no esmalte; facetas na dentina; facetas em metade da coroa e facetas em mais de 2/ 3 da coroa. Auto-questionário validado para o consumo de álcool e tabaco, com 29 perguntas foi respondido pelos dois grupos. Teste T e Exato de Fischer foram aplicados. Bruxismo foi mais freqüente entre tabagistas, tanto em homens (68,4%) como mulheres (56,8%). Entre os indivíduos com bruxismo, 82,6% relataram que gostariam de parar de fumar e aqueles que anteriormente tentaram (76,4%) sentiram-se mais estressados ao parar. O consumo de álcool também foi mais freqüente no grupo com bruxismo (66,5% no gênero feminino e 73,5% no masculino). 88,4% relataram consumir álcool “para lidar com o estresse de forma adequada”. Resultados sugerem associação positiva entre bruxismo, consumo de álcool e tabagismo.
Relação entre bruxismo e consumo de álcool e tabaco em estudantes brasileiros
Keywords: Stomatognathic system; Smoking; Alcoholism; Sistema estomatognático; Tabagismo; Alcoolismo